2016
DOI: 10.1364/oe.24.011793
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and measurement of the absolute level of power radiated by antenna integrated THz UTC photodiodes

Abstract: We determine the output impedance of uni-travelling carrier (UTC) photodiodes at frequencies up to 400 GHz by performing, for the first time, 3D full-wave modelling of detailed UTC photodiode structures. In addition, we demonstrate the importance of the UTC impedance evaluation, by using it in the prediction of the absolute power radiated by an antenna integrated UTC, over a broad frequency range and confirming the predictions by experimental measurements up to 185 GHz. This is done by means of 3D full-wave mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…We also performed 3D full-wave modelling of detailed UTC photodiode structures, as shown in Fig. 2, to achieve accurate knowledge of the UTC output impedance up to 400 GHz [6]. The model is very detailed, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed 3D full-wave modelling of detailed UTC photodiode structures, as shown in Fig. 2, to achieve accurate knowledge of the UTC output impedance up to 400 GHz [6]. The model is very detailed, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve high radiation power, the transition between the PD and the antenna needs to be carefully designed. It has been shown that impedance matching has a significant effect on the radiation power of integrated photonic emitters [24] and that maximum RF power can be extracted from the PD by conjugate impedance matching. In [25], a matching network was used to achieve conjugate matching between the MUTC PD and the Vivaldi antenna.…”
Section: Photonic Emitter At 100 Ghzmentioning
confidence: 99%
“…[27,[29][30][31][32][33], either a Teflon or Si lens was used to improve the directional gain of the antenna. Planar antenna structures include Yagi [34,35], bow-tie [18,24], and slot [29,35], however, impedance matching between PD and antenna was not reported for these structures. In contrast, the integrated photonic emitters reported in refs.…”
Section: Photonic Emitter At 100 Ghzmentioning
confidence: 99%
“…The total power emitted by an antenna depends on the impedance match with the driving source and the radiation efficiency. The absolute level of power emitted by an antenna over the frequency range can be calculated and predicted if the UTC impedance is known and the coupling efficiency between UTC and antenna taken into account [27] [28]. We presented a comprehensive study of UTC-PD output impedance and frequency photoresponse in [27].…”
Section: Antenna Integrated Waveguide Utc-pdsmentioning
confidence: 99%